COMPARATIVE ANALYSIS OF MARKET CONDITIONS OF GRAIN ECONOMY OF RK AND MONGOLIA - G.M. Mukasheva, G.M. Mukasheva; Aymurzina, B.T. (Academic Journal of Physical and Chemical Sciences, 2018)
According to the authors, the agriculture of both Kazakh and Mongolian peoples since ancient times was cattle breeding. Agriculture played a minor role, however, the agro-industrial complex is the leading sector of the economy of the Republic of Kazakhstan and Mongolia, whose main task is the cultivation of crops and the breeding of farm animals for the production of crop and livestock products. At the same time, implementation of state policy plays a major role in the development of livestock in two countries. Currently, the majority of Kazakhstani corporations are experiencing a lack of funds, as they are not able to update their production facilities, introduce the achievements of scientific and technological progress, and are forced to turn for help to the state.